Cost-effectiveness analysis of pneumococcal conjugate vaccine introduction in Paraguay. (7th May 2015) - Kieninger, Martha Peña; Caballero, Edgar Giménez; Sosa, Antonio Arbo; Amarilla, Carlos Torres; Jáuregui, Bárbara; Janusz, Cara Bess; Clark, Andrew David; Castellanos, Raúl Montesano
Highlights: The EPI in Paraguay assessed the cost-effectiveness and impact of pneumococcal conjugate vaccination with the TRIVAC model. When compared to no vaccination, both PCV10 and PCV13 represent good value for money. Cost-effectiveness and other impact metrics are critical for informed decision making. Abstract: Objective: To describe a cost-effectiveness analysis of 10- or 13-valent pneumococcal conjugate vaccine (PCV10 or 13) introduction in Paraguay compared to no vaccination. Methods: The integrated TRIVAC vaccine cost-effectiveness model (version 2.0) jointly developed by the Pan American Health Organization's ProVac Initiative and the London School of Hygiene & Tropical Medicine was applied from the government and societal perspectives to estimate the cost-effectiveness (CE) of PCV introduction during 2010 and 2011. The cost-effectiveness ratios of PCV10 and PCV13 were separately compared to non-vaccination. The model calculated health and economic benefits of vaccination for 10 birth cohorts of children <5 years of age. A base case scenario with two primary doses at 2 and 4 months and a booster dose at 12 months (2 + 1 schedule) and alternate scenarios with varying parameters were considered. Results: With PCV10 introduction, the incremental costs of the vaccination program would be approximately US$ 67 million to vaccinate all 10 cohorts of children; with PCV13, US$ 87 million. Health services costs avoided by the government with PCV10 would be US$ 19.5 million; with PCV 13, US$ 17.7 million. From the societal perspective, savings were much greater: with PCV10, US$ 43 million; with PCV13, US$ 35 million. For the higher priced PCV13, the average cost-effectiveness ratio was better than for PCV10 when compared to no vaccination, but regardless both were cost effective for government and society based on a threshold of 3× GDP per capita in Paraguay (2009 US$ 2516). The number of averted meningitis and all-cause pneumonia cases and deaths was greater with PCV13 than with PCV10 when compared to no vaccination. Conclusion: The introduction of either PCV10 or PCV13 would be cost effective when compared to no vaccination, and in some scenarios, highly cost effective in Paraguay. The outcomes of these analyses demonstrate that a pneumococcal vaccine could substantially reduce morbidity and mortality in children <5 years in Paraguay.